Variance Aware Optimization of Parameterized Queries - Chaudhuri, Surajit; Narasayya, Vivek; Lee, Hongrae (ACM SIGMOD, 2010)
Parameterized queries are commonly used in database applications. In a parameterized query, the same SQL statement is potentially executed multiple times with different parameter values. In today’s DBMSs the query optimizer typically chooses a single execution plan that is reused for multiple instances of the same query. A key problem is that even if a plan with low average cost across instances is chosen, its variance can be high, which is undesirable in many production settings. In this paper, we describe techniques for selecting a plan that can better address the trade-off between the average and variance of cost across instances of a parameterized query. We show how to efficiently compute the skyline in the average-variance cost space. We have implemented our techniques on top of a commercial DBMS. We present experimental results on benchmark and real-world decision support queries.